The anti-inflammatory potential of Portulaca oleracea L. (purslane) extract by partial suppression on NF-κB and MAPK activation. (30th August 2019) - Miao, Lingchao; Tao, Hongxun; Peng, Yu; Wang, Shengpeng; Zhong, Zhangfeng; El-Seedi, Hesham; Dragan, Simona; Zengin, Gokhan; Cheang, Wai San; Wang, Yitao; Xiao, Jianbo
Highlights: Purslane extract showed anti-inflammatory effect in RAW 264.7 cells. It reduced productions of NO, TNF-α and IL-6; and iNOS and COX-2 expressions. It inactivated NF-κB and MAPK signaling pathways. Abstract: Portulaca oleracea L. (Purslane) has great potential as food and traditional drugs in several countries. The purpose of this study was to evaluate the anti-inflammatory effects of purslane extract on lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. Purslane extracts significantly reduced LPS-induced synthesis of NO in a dose-dependent manner, as well as the expression levels of iNOS and COX-2. The productions of TNF-α and IL-6 were also significantly reduced at the higher dose of 400 μg/ml. Meanwhile, the expression levels of P65, p -P65, p -MEK and p -IκB-α were inhibited dose-dependently. The nuclear translocation of P65 was partially prevented by the extract, which explained the inhibition of NF-κB pathway. In addition, three reported flavonoids, named luteolin, kaempferol and quercitrin, were identified in the extract, which might be responsible for its anti-inflammatory effects. Above all, our research has partially proved that purslane could be considered as a natural anti-inflammatory agent in further applications.